Diversity of Ferns (Pteridophyta) in the Dieng Valley Tourism Area - Dilla Shafira Madania; Erlita Chandra Karina Putri; Helmi Adi Guna; Syifa’ Hajidah Aziz; Wulan Madya Rani; Indra Fardhani (Postgraduate, University of Mataram, 2025)
Indonesia is rich in biodiversity, especially in its flora. Biodiversity is the various forms of life that exist on land, air and water in a space and time, whether in the form of plants, animals, even the smallest living things such as microorganisms. One type of plant that has a lot of biodiversity in Indonesia is ferns (Pteridophyta). Ferns are Cormophyta spore plants that can live in various habitats, either as epiphytes, terrestrial plants, or as aquatic plants. The purpose of this study was to determine the diversity of ferns in the Dieng Valley. Daui District, Malang Regency. The research method used is a descriptive method with a purposive sampling technique, namely sampling based on certain criteria. Data collection was carried out through the exploration method, where researchers made direct observations of fern species (Pteridophyta). Species identification was carried out using the Picture This and Google lens applications. Data analysis was carried out by calculating the Diversity Index. The results of the study obtained were that in the Dieng Valley area, the pteris vittata species was found to be more dominant. These ferns were found in various research locations.